2011
DOI: 10.1007/s12539-011-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking studies of curcumin analogs with phospholipase A2

Abstract: The enzyme phospholipase A2 is responsible for the hydrolysis of membrane phospholipids that release arachidonic acid, which serves as a substrate for pro-inflammatory mediators, such as prostaglandins and leucotriens. The binding of the substrate to PLA2 occurs through a well-formed hydrophobic channel. So blocking the hydrophobic channel is an effective way to inhibit PLA2. Compounds inhibiting PLA2 have been implicated as potential therapeutic agents in the treatment of inflammation related diseases. Curcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…•THC was more active than curcumin in binding to phospholipase (PLA) 2 [74] •THC was more active than curcumin in preventing azoxymethane-induced colon carcinogenesis [75].…”
Section: Studies Showing Thc To Be More Active Than Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…•THC was more active than curcumin in binding to phospholipase (PLA) 2 [74] •THC was more active than curcumin in preventing azoxymethane-induced colon carcinogenesis [75].…”
Section: Studies Showing Thc To Be More Active Than Curcuminmentioning
confidence: 99%
“…Compounds inhibiting PLA2 have been implicated as potential therapeutic agents in the treatment of inflammation-related diseases. Dileep et al [74] used molecular modeling and docking to compare the binding of THC to PLA2 with the binding of curcumin to PLA2 and found that THC exhibits better binding energy than curcumin. The effects of curcumin and THC on Nω-nitro-L-arginine methyl ester (L-NAME)-induced hypertension and oxidative stress in rats were examined by Nakmareong et al [61], who found that THC was more potent than curcumin as an antihypertensive agent.…”
Section: Anti-inflammatory Activitiesmentioning
confidence: 99%
“…In an effort to knockout cPLA2 activity from a pharmacological standpoint, several curcumin analogs, identified as rosmarinic acid, tetrahydrocurcumin, dihydrocurcumin and hexahydrocurcumin, have been discovered that can inhibit the PLA2 hydrophobic binding pocket from binding substrate thereby preventing the release of AA and downstream metabolic events [169]. Extracts from the white oatmeal Avena sativa can also attenuate the stimulated mobilization of AA in keratinocytes, though not completely, through the reduction of PLA2 transcription and protein production [170].…”
Section: Targeting Lipid Pathwaysmentioning
confidence: 99%
“…The anti-inflammatory properties of curcumin have been explained by Chainani-Wu (2003) and Menon and Sudheer (2007). The binding of curcumin and its analogues at the active site of PLA 2 has already been demonstrated by molecular modelling and docking studies (Nirmal et al 2008;Dileep et al 2011). Curcumin-induced inhibition of tumorigenesis in mice has been reported by Srimal and Dhawan (1973) and Huang et al (1997).…”
Section: Introductionmentioning
confidence: 95%
“…However, only 2-methoxycyclohexa-2-5-diene-1,4-dione (MCW) was observed in the crystal structure, which is actually the photodegraded product of curcumin and is bound at the active site of PLA 2 . In our previous report (Dileep et al 2011), we focused on comparing the binding energies of different curcumin analogues. In the present study, we have compared the binding mode of the docked curcumin structure with its photodegraded product.…”
Section: Introductionmentioning
confidence: 99%